Resolving atomic-scale phase transformation and oxygen loss mechanism in ultrahigh-nickel layered cathodes for cobalt-free lithium-ion batteries - Wang, Chunyang; Han, Lili; Zhang, Rui; Cheng, Hao; Mu, Linqin; Kisslinger, Kim; Zou, Peichao; Ren, Yang; Cao, Penghui; Lin, Feng; Xin, Huolin L. (Matter, 2021)
Doped LiNiO2 has recently become one of the most promising cathode materials for its high specific energy, long cycle life, and reduced cobalt content. Despite this, the degradation mechanism of LiNiO2 and its derivatives still remains elusive. Here, by combining in situ electron microscopy and first-principles calculations, we elucidate the atomic-level chemomechanical degradation pathway of LiNiO2-derived cathodes. We uncover that the O1 phase formed at high voltages acts as a preferential site for rock-salt transformation via a two-step pathway involving cation mixing and shear along (003) planes. Moreover, electron tomography reveals that planar cracks nucleated simultaneously from particle interior and surface propagate along the [100] direction on (003) planes, accompanied by concurrent structural degradation in a discrete manner. Our results provide an in-depth understanding of the degradation mechanism of LiNiO2-derived cathodes, pointing out the concept that suppressing the O1 phase and oxygen loss is key to stabilizing LiNiO2 for developing next-generation high-energy cathode materials. [Display omitted] •O1 phase acts as a preferential nucleation site for rock-salt transformation•O1 → rock-salt transformation involves cation mixing and shear along (003) planes•Cracks initiating from both particle surface and interior are identified in 3D•Concurrent rock-salt transformation is identified in both open and internal cracks High-Ni and low-Co or Co-free layered cathode materials have resurfaced as the subject of intensive research within the battery community, as a result of the tripled cost and a speculated worldwide shortage of cobalt—a main component within the cathodes of lithium-ion batteries (LIBs). Despite improved capacity and lower costs, LiNiO2 and LiNiO2-based high-Ni cathodes still suffer from a complex chemomechanical degradation that has eluded researchers so far. Here, we resolve the atomic-scale phase transition and cracking pathways in LiNiO2 and doped LiNiO2 using in situ microscopy, electron tomography, and first-principles calculations. Our results will have a significant impact on the basic understanding of the chemomechanical degradation of ultrahigh-nickel layered cathodes in general, as well as provide useful guidance for optimizing LiNiO2-derived materials for practical applications. By using in situ and 3D electron microscopy, we decipher the chemomechanical degradation pathway of LiNiO2-based ultrahigh-nickel layered cathodes for lithium-ion batteries. We reveal that the O1 phase acts as a preferential nucleation site for rock-salt transformation via a two-step pathway involving cation mixing and shear along the (003) plane. Two types of cracks initiating from both the particle surface and interior as well as concurrent rock-salt phase transformation are uncovered. Our results provide deep understanding of the degradation mechanism of LiNiO2-derived cathodes.